Corporate Social Responsibility and Discrimination - Ardito Vega, Wilfredo (2010)
Although the Peruvian State has promulgated norms to stop the discrimination in the labor and business scope even its implementation is deficient. In this way, it is the companies themselves that must carry out internal policies to apply those standards. The author, initially, addresses the development of discrimination in Peru within a phenomenon of naturalization of discrimination and from there as it becomes internalized by eliminating its own elements. Starting from treating differently those who are in a different condition. And when differentiations are made between individuals and these are for objective and reasonable justifications. In the second part, the author addresses the legal framework against discrimination in Peru. To this end, it will refer to labor discrimination, discrimination against consumers, and the criminal treatment of discrimination. And in the face of all this legal scenario is complex compliance with that regulation because of the various factors that the author will explain. In the third part, it will be developed how discrimination must also be faced by companies and hence their corporate social responsibility. This could be reflected in an adequate recruitment policy plan, attention to the public and internal policies in accordance with the prevention of discrimination. Added to this, the concern about the lack of regulation regarding advertising is also relevant.